Fasciolopsis buski sebagai Penyakit Tropis Terabaikan: Perspektif Pendekatan One Health dalam Pencegahan dan Pengendalian - Suriyani Suriyani; Sisca Sisca; Yani Kurniawan; Monica Dwi Hartanti; Triasti Khusfiani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Fasciolopsiasis is a parasitic disease caused by Fasciolopsis buski and remains a public health concern in several Asian regions, particularly in areas with poor sanitation and inadequate environmental conditions. This study aimed to examine fasciolopsiasis from a One Health perspective by highlighting its epidemiology, risk factors, public health impacts, and disease control strategies. This study employed a literature review approach by collecting scientific articles from PubMed, Scopus, ScienceDirect, and Google Scholar published between 2020 and 2025. The selected literature was analyzed descriptively and qualitatively using a thematic approach based on human, animal, and environmental components within the One Health framework. The findings indicate that the transmission of F. buski is influenced by the consumption of raw aquatic plants, poor personal hygiene, inadequate environmental sanitation, the presence of snails as intermediate hosts, and pigs as animal reservoirs. Chronic infection not only causes gastrointestinal disorders but also affects nutritional status, quality of life, and community productivity. Control strategies focusing solely on individual treatment are considered insufficient to interrupt disease transmission effectively. The One Health approach provides a more comprehensive framework through the integration of human health, animal health, and environmental management. Therefore, fasciolopsiasis control should be implemented through integrated strategies, including sanitation improvement, health education, monitoring of animal reservoirs, and aquatic environmental management to achieve more effective and sustainable disease control.